The old Syriac inscriptions of Edessa and Osrhoene : texts, translations, and commentary - Drijvers, H. J. W.; Healey, John F. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
This volume contains all the known Old Syriac inscriptions from Edessa and the area around Osrhoene in Northern Mesopotamia from the first three centuries C.E., the number of which has substantially increased over the last decades. The texts are given in estrangelo script and are accompanied by an extensive philological and historical commentary. The originals are presented in photographs and line drawings. The volume also contains chapters on the script of these inscriptions, on the language and on the history and culture of Edessa. Two appendices offer the texts of three parchments written in Syriac and originating from the same area, and of known but still unpublished inscriptions. The book concludes with indices of words and proper names, which are complement to the Dictionary of the North-West Semitic Inscriptions ( Brill , 1995), and with a full bibliography.